DEGRADASI RETORIKA TOKOH MASYARAKAT KELURAHAN IJOBALIT ( KAJIAN SOSIOLINGUISTIK ) - Fauzi, Rizwan; Nursaly, Baiq Rismarini; Taufiq, Muh. (BISAI: Jurnal Bahasa, Sastra, dan Pengajaran, 2025)
This research aims to describe the forms and factors that influence the degradation of rhetoric used by community leaders in Ijobalit Village, using a sociolinguistic approach. This research is a qualitative descriptive research. The population in this study were community leaders and the local community, with informants consisting of 12 people. The techniques used for data collection are observation, interviews and recording techniques. The research results show that the rhetoric used by community leaders in conveying information or appeals to the public tends to take the form of monologues. In this context, communication is carried out by one person via loudspeakers in the mosque or prayer room. This research uses Ardiansyah's theory which states, "rhetoric is the science of the art of speaking effectively, describe phenomena that occur.